Sagsbehandling i en digital virkelighed: Digitalisering, standardisering og individuelle hensyn - Høybye-Mortensen, Matilde (Politik, 2012)
The Danish digitisation strategy states that case management systems are one of the means to digital welfare. is article examines Fælles Sprog (common language) which is used by case managers within the area of care for the elderly. Based on interviews the article illustrates how cross pressures from concerns of the in- dividual needs of the clients on the one hand and the system requirements for standardisation on the other hand are handled by the street level bureaucrats. In this way, the article presents e-government in practice within social welfare provision.